Textbook Evaluation: Models of Checklist Methods - Linda Budiarsih (Proceedings International Conference on Teaching and Education (ICoTE), 2022)
This paper describes the aspects that should be considered in developing a checklist for textbook evaluation. Those aspects covered the general description about the role of textbook, the reason in doing the textbook evaluation, the development of checklist textbook evaluation, and also some models of checklist methods from some experts are also conveyed. The models of development of checklist in textbook evaluation are developed in some articles, they are:  Afshin Soori, Reza Kafipour, and Mohammad Soury (2011), Monteser Mohamed Abdel Wahab (2013), Beatriz Lopez Medina (2016), Niwat Wuttisrisiriporn and Siriluck Usaha (2019). A descriptive qualitative method is used in writing this article. It describes the model of checklist evaluation as an instrument for textbook evaluation.  The discussion will be based on some criteria such as: the criteria used in the checklist and the special features of checklist. Hopefully, the models of textbook checklists in this article can be beneficial by the teachers or the evaluators in order to find some references to develop their own criteria of textbook evaluation that is suitable with their own needs and classroom setting.